Pneumothorax and Pneumomediastinum in SARS-CoV-2 Infection - Cătălina Aldea; Irina Mihaela Abdulan; Bogdan Mihnea Ciuntu; Robert Negru; Cătălina Mihaela Luca (Medicina)
Background and Objectives: Infection with SARS-CoV-2, the etiologic agent of Coronavirus 2019, spread rapidly globally after the first case was reported in Wuhan, China. Multiple respiratory complications, including pneumothorax and pneumomediastinum, have been observed. This study presents an analysis of 100 patients diagnosed with these conditions in the context of SARS-CoV-2 infection. Materials and Methods: This study was conducted between March 2020 and February 2021 and included patients from two hospital units designated for the management of patients with SARS-CoV-2 infection. Demographic data, laboratory investigation results, imaging assessments, medical-surgical management strategies, and survival data were recorded. Results: The study included 100 patients with confirmed SARS-CoV-2 infection (mechanically ventilated and non-ventilated). Of these, 57 patients presented with pneumothorax, 26 of whom also had associated pneumomediastinum and 43 of whom were diagnosed with pneumomediastinum alone. There was a higher incidence of pneumothorax among male patients. Also, 22 patients had concomitant subcutaneous emphysema. Regarding therapeutic management, 36 pleural drains were performed. Bilateral pneumothorax was identified in five patients. Conclusions: The presence of pneumothorax was correlated with a decreased survival rate among patients diagnosed with COVID-19. Also, performing pleural drainage in patients with pneumothorax and COVID-19 pneumonia did not significantly influence the prognosis of the underlying disease.